Assessing School Engagement – Adaptation and Validation of “Engagement Versus Disaffection With Learning: Teacher Report” in the Swedish Educational Context - Ritoša, Andrea; Danielsson, Henrik; Sjöman, Madeleine; Almqvist, Lena; Granlund, Mats (Frontiers in Education, 2020)
To follow the trajectories of children’s engagement in learning, validated measures of engagement appropriate for different ages and educational contexts are needed. The purpose of this study was to adapt and validate the school engagement questionnaire (Engagement Versus Disaffection with Learning: Teacher Report, EDL) in the Swedish educational context, and to investigate if it assesses the same construct as a measure of engagement used for children of preschool age. After translating the questionnaire to Swedish, cognitive interviews were conducted with six teachers to check for interpretability and relevance of the items. For psychometric validation, teachers of 110 six to seven-year-old children filled out EDL on two occasions two weeks apart. On the first occasion, they also filled out the Child Engagement Questionnaire, a measure of global engagement intended for children of preschool age. Dimensional structure, convergent validity, test-retest reliability, and internal consistency of EDL were investigated. Factor analysis provided support for differentiating between behavioral and emotional components of school engagement. Measures of school and preschool engagement used in this study correlated highly, which provides support for using them to study the engagement of children as they develop, and their educational contexts change. The subscales of behavioral and emotional engagement showed good test-retest reliability and internal consistency.